2006
DOI: 10.1128/jcm.01724-06
|View full text |Cite
|
Sign up to set email alerts
|

Brain Abscess Caused by Streptococcus pyogenes in a Previously Healthy Child

Abstract: Responsible for many childhood diseases, group A Streptococcus (GAS) is a rare cause of central nervous system infections. We report the case of a previously healthy boy with brain abscesses caused by M/ emm type 12 GAS and review the case in the context of the published literature and recent epidemiological data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Intracranial infections caused by S. pyogenes are unusual and nearly always associated with significant meningitis or a contiguous focus. 1-3 Crum 4 and Dehority et al 5 reported a 22-year-old male and a 17-month-old female, respectively, with S. pyogenes brain abscesses following otitis media.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial infections caused by S. pyogenes are unusual and nearly always associated with significant meningitis or a contiguous focus. 1-3 Crum 4 and Dehority et al 5 reported a 22-year-old male and a 17-month-old female, respectively, with S. pyogenes brain abscesses following otitis media.…”
Section: Discussionmentioning
confidence: 99%
“…There have been five cases reported in the literature regarding brain abscess caused by Streptococcus pyogenes and all had a better prognosis than those caused by the more common CNS pathogens. None of the reported cases had a history of penetrating injury to the cranium 10,11,14,17,21) . We believe that penetrating skull injury has a high risk regarding development of an intracranial abscess.…”
Section: Discussionmentioning
confidence: 99%
“…Med-based search. Two had otitis media while three had no predisposing factors or trauma 10,11,14,17,21) . Our case is the first reported brain abscess caused by penetrating skull injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abscess formation at other sites occurs rarely. Cases of abscesses with S. pyogenes in the brain (6,7,9,17), in the epidural space (10,16), in the mediastinum (5), in the lung (8), in the spleen (4), in the retroperitoneum (11), in the pericolic tissue (15), in muscular tissue (1,3,18), and in periprosthetic breast tissue (14) have been reported. Considering how common S. pyogenes infections are, abscess formation at sites other than those around the tonsils is distinctly uncommon.…”
Section: S Pyogenes or Group A Streptococcusmentioning
confidence: 99%